Gambaran Penanganan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Jagir Kota Surabaya - Tamya Amiratus Sholihah; Akas Yekti Pulih Asih; Aviana Gita Lara (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
One of the nutritional problems that is currently a concern of the government is stunting. In 2020 the prevalence of stunting in the world is reported to reach 149.2 million children (22%). Based on World Bank data for 2020, the incidence of stunting in Indonesia ranks 115th out of 151 countries in the world and 3rd in the Southeast Asia Region. The purpose of this study is to find out the description of the handling of stunting in toddlers in the Working Area of the Jagir Health Center, Surabaya. The analysis used was univariate analysis by looking at the distribution of the frequency of stunting under five. The results of research on the nutritional status of toddlers based on the percentage of height for age showed that as many as 0.6% (15 toddlers) were found to be stunted, which was divided into two categories, namely short and very short in the Working Area of the Jagir Health Center, Surabaya, spread across 3 urban villages. Based on the percentages for December 2022 - February 2023, there was a decrease in stunting toddlers who were found. Treatment  carried out to reduce stunting rates at the Jagir Health Center are monitoring body weight and height through home visits, providing stunting food in the form of animal protein assisted by KSH to deliver stunting food and monitoring the food until it is consumed, providing KIE to family members, as well as coordination with cross-sectors if there are obstacles related to non-health problems.